ОСОБЛИВОСТІ ВИКОРИСТАННЯ АВТОНОМНИХ ВИМІРЮВАЛЬНИХ ПЕРЕТВОРЮВАЧІВ ДЛЯ ДІАГНОСТУВАННЯ ЕЛЕКТРОТЕХНІЧНОГО ОБЛАДНАННЯ З УРАХУВАННЯМ РЕЖИМІВ ЙОГО РОБОТИ - Герцик, С.М.; Гижко, Ю.І.; Зварич , В.М.; Мислович , М.В.; Остапчук , Л.Б.; Сисак , Р.М. (Інститут електродинаміки НАН України, Київ, 2018)
The structure of the diagnostic system is proposed, in which the Energy Harvesting (EN) technology is used to provide the functioning of autonomous measuring transducers located on the parts of the electric machines (EM), which provides an opportunity to provide the power supply of electronic circuits in autonomous vibration measurement devices by converting into electric current of the mechanical energy of the vibration of the EM unit. On the examples of studying the vibrations of the charged magnetic circuit, the necessity of forming the spaces of diagnostic features is taken into account, taking into account the operating modes of the objects being studied. The obtaining of experimental data is carried out using a laboratory sample of the diagnostic system, which includes measuring transducers, the functioning of which is provided by autonomous power systems. References 10, tables 2, figures 3.